Psoriasis as an Immune-Mediated and Inflammatory Systemic Disease: From Pathophysiology to Novel Therapeutic Approaches - Anna Campanati (MDPI AG, 2021)
Psoriasis is an immune-mediated inflammatory disease, with a chronic relapsing-remitting course, which affects 2–3% of the worldwide population. The progressive acquisitions of the inflammatory pathways involved in the development of psoriasis have led to the identification of the key molecules of the psoriatic inflammatory cascade. At the same time, psoriasis therapy has radically evolved with the introduction of target molecules able to modify the natural history of the disease, acting specifically on these inflammatory pathways. For these reasons, biologics have been demonstrated to be drugs able to change the disease’s natural history, as they reduce the inflammatory background to avoid irreversible organ damage and prevent systemic complications. However, several issues related to the use of biologics in patients with systemic comorbidities, remain open. All these data reflect the extraordinary potentiality of biologics, but also the unmet medical need to improve our knowledge on the long-term risk related to continuous use of these drugs, and their administration in special populations. This narrative review aims to highlight both the efficacy and safety profile of biologics in psoriasis, starting from pathophysiology and moving towards their clinical application.